Evaluation of the immediate outcomes of perinatally asphyxiated newborns in a tertiary care hospital in rural Bangalore: a retrospective study - Chikkanna, Somashekhar; P., Saravanan; M. V., Nagaraj; S., Kavya (International Journal of Contemporary Pediatrics, 2020)
Background: Perinatal asphyxia is a condition resulting from deprivation of oxygen to a neonate that lasts long enough to cause damage to the brain. Perinatal asphyxia is one of the major causes of early neonatal mortality in India. The goal was to evaluate outcomes of asphyxiated babies. Methods: One hundred consecutive neonates with birth asphyxia (Apgar 0-3 at 5-minute of age) were studied. Data from medical records of all babies with perinatal asphyxia admitted were retrieved and documented for the study. Results: Majority of the neonates are inborn (57%). Male to female ratio was 1.5:1. Spontaneous vaginal delivery constitute 32% and lower segment caesarean section (LSCS) 36%. Mortality was highest in hypoxic ischemic encephalopathy (HIE) stage 3 with 11%. Mean duration of hospitalization is directly related to Sarnat and Sarnat staging of HIE. 22% babies were having neurological sequelae and discharged on anti-convulsant. 21% mortality, majority were outborn. Conclusions: Despite advances in the management of neonates, perinatal asphyxia is still the leading cause of morbidity and mortality. Perinatal asphyxia is still prevalent despite medical advances. Babies with HIE stage III had poor outcome. Appropriate strategies required to minimize the neuro-developmental sequelae.